SISTEM APLIKASI POIN OF SALE (POS) UNTUK PENJUALAN TOKO NAILA COOKIES BERBASIS JAVA - Prastomo, Andi; Alfarisi, Salman (Journal of Information System, Applied, Management, Accounting and Research, 2024)
The Java-based Point of Sale (POS) application system was created to increase operational efficiency and transaction accuracy at Naila Cookies Shop. This system automates sales processes, inventory management, and financial reporting, aiming to speed up the checkout process, minimize errors, and provide real-time sales data. Utilizing Java as the main programming language with an object-oriented approach ensures scalability and ease of maintenance. Additionally, the system has a user-friendly interface to facilitate fast and efficient transactions for store staff. Testing shows important improvements in transaction speed and accuracy, potentially reducing long-term operational costs. These findings show the positive impact of the appropriate use of information technology on retail store operations.